Wojciech Stanisław Chrościński (ok. 1660-po 1733) — człowiek i dzieło - Teusz, Leszek (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'MS Mincho'; mso-ansi-language: EN-GB; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-GB">The article discusses the figure and the work of the poet from the Saxon times in Poland. The first part of the article presents some essential biographical data and his most important literary achievements – from his debut poem Trąba wiekopomnej sławy..., through the translations of the Latin works of Ovid and Lucan, to poems written in the Polish language, such as Biblical poems and other cycles of poems. The other part of the article includes a discussion on the history of the reception of Chrościński’s works and the opinions on his literary output given by literary critics and contemporary historians of literature. Diverse and not equivocal opinions emerge – from decidedly favourable to those more restrained and even critical. However, the popularity of the poems written by Chrościński in the seventeenth and the eighteenth centuries is remarkable. This popularity wanes in the course of time and slowly but steadily he becomes an unknown author, rarely recalled and selectively cited. The varied and divergent attitudes of historians of literature make us fully accept the following opinion given by Brückner: “Chrościński highly deserves a closer study of his literary output”. Accordingly, the latter postulate is an invitation to a thorough and deepened investigation of the works of the poet.